Simulation of a PMSM Motor in COMSOL Environment - Kovács, G. (Acta Technica Jaurinensis, 2012)
The paper presents simulation results of a two-dimensional Permanent Magnet Synchronous Motor (PMSM, PMS motor), which were calculated by the help of the Infolytica MotorSolve and of the COMSOL Multiphysics, as well. The simulation results were compared with each other focusing on the torque, the magnetic flux density and the magnetic potential of the PMSM motor.